2016
DOI: 10.1007/s40258-016-0289-3
|View full text |Cite
|
Sign up to set email alerts
|

Screen Time and Health Indicators Among Children and Youth: Current Evidence, Limitations and Future Directions

Abstract: Despite accumulating evidence linking screen-based sedentary behaviours (i.e. screen time) with poorer health outcomes among children and youth <18 years of age, the prevalence of these behaviours continues to increase, with roughly half of children and youth exceeding the public health screen time recommendation of 2 h per day or less. The purpose of this article is to provide an overview of key research initiatives aimed at understanding the associations between screen time and health indicators including ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
5
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 66 publications
6
111
5
5
Order By: Relevance
“…Amounts of screen time and mental health are related (3,37), most probably bi-directionally: poorer initial mental health predicts higher screen time (and declining physical activity levels), whilst increases in anxiety are associated with increasing screen time (8,38,39). Compared to children, we identi ed that proportionally fewer adolescents met the screen time recommendations, in agreement other Australian population studies (22) and international ndings (9). This reinforces adolescence as a particularly critical time for reducing mental health related risk behaviours.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Amounts of screen time and mental health are related (3,37), most probably bi-directionally: poorer initial mental health predicts higher screen time (and declining physical activity levels), whilst increases in anxiety are associated with increasing screen time (8,38,39). Compared to children, we identi ed that proportionally fewer adolescents met the screen time recommendations, in agreement other Australian population studies (22) and international ndings (9). This reinforces adolescence as a particularly critical time for reducing mental health related risk behaviours.…”
Section: Discussionsupporting
confidence: 87%
“…Investigations into unhealthy lifestyle behaviours have shown that they contribute to poorer health related quality of life and have a prolonged negative in uence on psychological health (2,(6)(7)(8). Increased electronic screen time is an issue of growing concern across all developed countries (9,10), due to evidence of its contribution to increased sedentary behaviour and a host of other undesirable outcomes, including poorer quality of life and behavioural and psychological di culties (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…This so called screen-based sedentary behavior has been associated with a range of adverse health consequences [12, 13]. even independently of their impact on PA [14], such as adiposity, aerobic fitness, quality of life, self-esteem, pro-social behavior, academic achievement, depression and anxiety [15]. Other authors conclude that there is not enough data available to draw conclusions on this issue, specifically if children and adolescents are sedentary but active at the same time [16].…”
Section: Introductionmentioning
confidence: 99%
“…Tiene también consecuencias negativas para la salud mental, en especial problemas de inatención en los más pequeños (3), y en adolescentes (4), en los que tienen especial protagonismo las redes sociales (5). Hay suficiente información disponible que apunta a que el tiempo de consumo de pantallas se asocia de una forma negativa a mayor adiposidad, peor condición física, pero calidad de vida, menor autoestima, pero rendimiento académico y pérdida de habilidades sociales, mayor grado de ansiedad y de depresión (6). Por el contrario, la práctica regular de actividad física se asocia a un mayor bienestar y a un mejor estado de salud mental (7,8).…”
Section: Editorialunclassified